Successful Vitrification of In vivo Embryos Collected from Superovulated Japanese Black Cattle (Wagyu). Issue 2 (7th February 2016) - An, L; Ling, PP; Zhu, X; Liu, Y; Zhang, F; Ma, X; Xu, B; Wang, Y; Du, Z; Yang, L; Xue, F; Bella, A; et al.
Content: The aim of this study was to determine whether vitrification is an effective method when used for Japanese Black Cattle (Wagyu) in vivo‐ derived embryos, collected following a superovulation treatment and embryo transfer (MOET) programme. In vivo ‐derived morula and blastocysts collected on day 7 after artificial insemination, were vitrified using a modified droplet vitrification (MDV) procedure and subsequently warmed for transfer (ET) into synchronized recipients. Fresh embryos, and embryos cryopreserved using a standardized slow freezing procedure (direct thaw/direct transfer, DT) served as ET controls. Two different follicle‐stimulating hormone (FSH) sources, Folltropin ® Canada (FSH BAH, 24 donors) and a brand prepared by the Chinese Academy of Science (FSH CAS, 16 donors), were compared in a series of superovulation outcomes following well‐established FSH administration protocols. Following data analysis, the total number of ovulations recorded at the time of embryo flushing (10.5 vs 8.5; p = 0.28) and the total number of transferable embryos (6.2 vs 5.1; p = 0.52) were similar between the two FSH sources. ET for MDV (39.7%, n = 78), DT (35.2%, n = 71) and fresh controls (47.1%, n = 34) resulted in similar pregnancy rates (p > 0.05). When MDV was used, a higher pregnancy rate (42.6%) resulted from the transfer of vitrified morulae, when compared to the DT counterparts (24.3%), (p = 0.05). Transfer of vitrified morulae resulted also in higher pregnancy rate, when compared to the transfer of vitrified blastocysts (42.6% vs. 29.4%; p < 0.05). Transfer of DT blastocysts resulted in higher pregnancy rate than morulae, similarly cryopreserved (47.1% vs. 24.3%, p < 0.05). In conclusion, MDV is an effective alternative methodology for cryopreservation of in vivo ‐derived embryos. This study gives also indication that, compared to vitrified blastocysts, MDV of morula stage embryos results in higher pregnancy rates following warming and transfer into synchronized recipients.